Preparation method and application of Cu-based nanocarrier with multiple stimulus-responsive degradability
By designing multiple stimulus-responsive degradable CuS@TA nanocarrier, loading DSF, and releasing Cu2+ and DSF in situ of tumors, the problem of insufficient stimulation response of existing copper-based nanocarriers is solved, and efficient anti-tumor treatment effect is achieved and good biocompatibility.
Patent Information
- Application Number
- CN202310346331.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The existing copper-based nanocarriers have too single stimulation response and are unable to efficiently release Cu2+ and DSF in situ in the tumor, resulting in poor treatment results.
A Cu-based nanocarrier CuS@TA, which is multi-stimulus-responsive, is designed to carry DSF, and release Cu2+ and DSF through endogenous acid response and thermal stimulation to form Cu(DTC)2 with anti-cancer activity.
It has achieved efficient release of Cu2+ and DSF in the tumor in situ, significantly improving the anti-tumor effect, the tumor suppression rate reaches 80%, and has good biocompatibility and photothermal heating performance.
Smart Images

Figure CN116327709B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine technology, and in particular to a preparation method and application of a Cu-based nanocarrier with multi-stimulus responsive degradability. Background Art
[0002] Cancer is a major disease that endangers the life and health of human beings worldwide, and its morbidity and mortality rate are increasing year by year. Among the existing cancer treatment methods, drug chemotherapy is still one of the most important means in clinical practice. Although a large number of anticancer drugs have been used in clinical practice, there are still disadvantages such as poor drug solubility, low biological activity, easy to produce systemic toxicity and multidrug resistance, which greatly limits the overall treatment effect of cancer. Photothermal therapy (PTT) is a typical phototherapy. Because of its negligible invasiveness, low toxicity and high selectivity, it has become one of the emerging cancer treatment methods in recent years. PTT can use photothermal converters to convert the light energy induced by near-infrared laser irradiation into heat energy at the tumor site, and kill tumor cells in the form of thermal therapy. A large number of photothermal materials with near-infrared light absorption have been applied to PTT, including metal sulfides, Prussian blue and gold nanomaterials. These photothermal materials have good stability and long half-life in the blood circulation, can be effectively enriched in the tumor lesion area, show high permeability and retention effect, and then gather at the tumor site through the retention effect to kill cancer cells using photothermal effect. However, its disadvantage is that it is easy to cause heat shock reaction in the body during the hyperthermia treatment, resulting in a significant decrease in the treatment effect. Therefore, researchers have tried to combine chemotherapy and photothermal therapy for cancer treatment. This strategy is widely used because it enhances the cancer treatment effect while producing negligible toxic side effects.
[0003] In recent years, the development of nanotechnology has greatly promoted the precision treatment of cancer and the delivery of chemotherapeutic drugs. A large number of inorganic or organic materials have been designed as nanocarriers to overcome the shortcomings of traditional chemotherapy, especially nanocarriers with tumor microenvironment (TME) response characteristics. Then, according to the different properties of nanocarriers, clinical chemotherapeutic drugs or chemotherapeutic drugs with potential anti-cancer activity are delivered to the tumor site, forming an intelligent nanotherapy platform with multiple therapeutic effects. Compared with traditional drug delivery systems, new drug delivery carriers have better tumor targeting enrichment characteristics and can effectively improve the accuracy and safety of tumor treatment. Therefore, in situ synthesis of chemotherapeutic drugs in tumor cells has gradually become an effective strategy to achieve tumor-specific treatment.
[0004] Disulfiram (DSF) is an FDA-approved clinical drug that is widely used in the treatment of chronic alcoholism. Preclinical and clinical research results show that DSF is a potential cancer chemotherapy drug, especially for the treatment of breast cancer. The anticancer activity of DSF is mainly achieved by chelating with divalent transition metal ions, especially divalent copper ions to form copper complexes. Under physiological conditions, DSF is easily metabolized to diethyldithiocarbamate (DTC) and combines with Cu 2+ Chelation forms a Cu / DSF complex copper-diethyldithiocarbamate (Cu(DTC)2), which further binds to nuclear localization protein 4 and induces its aggregation, inhibiting the p97-NPL4-UFD1 pathway and leading to cancer cell death. At the same time, during the formation of Cu(DTC)2, it will also cause a significant increase in the level of intracellular reactive oxygen species, which will then bind to macromolecules such as DNA to cause organelle dysfunction and ultimately induce tumor cell apoptosis. Therefore, by constructing a suitable nanocarrier and utilizing the characteristics of TME, Cu can be released in situ in the tumor. 2+ and DSF to generate the drug Cu(DTC)2 with anticancer activity to exert antitumor effects, which is a strategy with good application prospects. 2+ Great progress has been made in the construction of nanocarriers for co-delivery of DSF and Cu. 2+ The self-supplied and tumor-specific functional nanomaterial (DSF@PEG / Cu-HMSNs NPs) generates Cu(DTC)2 with anticancer activity in situ under the stimulation of slightly acidic conditions at the tumor site, and exerts a good tumor treatment effect in vivo and in vitro. Liu et al. designed a multifunctional nanotherapy platform DSF@PEG-HCuSNPs based on DSF. After reaching the tumor lesion area, the nanodrug responds to the stimulation of slightly acidic conditions and releases Cu 2+ It rapidly chelates with DSF in situ to form Cu(DTC)2, achieving DSF-based chemotherapy-synergistic photothermal therapy. 2+ This strategy is effective for enhancing the chemotherapy effect of DSF. Although the construction of copper-based nanocarriers for DSF loading has made good progress, its disadvantage is that the stimulus responsiveness of the constructed copper-based nanocarriers is too single. Therefore, it is urgent to design and construct copper-based nanocarriers with multiple stimulus responsive and degradable properties, and realize efficient loading of DSF, thereby releasing high concentrations of Cu in situ in the tumor. 2+ Combined with DSF, it can be effectively converted into highly toxic Cu(DTC)2 to achieve specific tumor treatment. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of a Cu-based nanocarrier with multiple stimulus-responsive degradability. The Cu-based nanocarrier CuS@TA of the present invention is loaded with DSF to form a nanomedicine (DSF-CuS@TA), which has a good appearance and uniform particle size distribution, and shows great potential in tumor treatment effect under the combined treatment of in situ chemotherapy and photothermal therapy.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows:
[0007] A method for preparing a Cu-based nanocarrier with multiple stimulus-responsive degradability comprises the following steps:
[0008] (1) Weigh 0.1-0.2 g of copper salt and 2-4 g of PVPK30 (polyvinyl pyrrolidone) and dissolve them in 15-25 mL of ultrapure water, and stir them with a magnetic stirrer at room temperature until they are fully dissolved to obtain a mixed solution I;
[0009] (2) 45-55 mg TA (tannic acid) and 0.7-0.8 g Na2S2O3·5H2O were dissolved in 10-15 mL ultrapure water to obtain TA solution and Na2S2O3·5H2O solution respectively;
[0010] (3) slowly adding 8-15 mL of TA solution dropwise to the mixed solution I under stirring to obtain a mixed solution II;
[0011] (4) adding 8-15 mL of Na2S2O3·5H2O solution to the mixed solution II, stirring evenly, and then quickly transferring to a reaction kettle for heating. After the temperature rises to 130-150°C, the reaction is continued for 5-8 hours to obtain a mixed solution III;
[0012] (5) The mixed solution III is naturally cooled to room temperature, filtered, and the filtrate is centrifuged to separate the precipitate, which is washed with ultrapure water for 2 to 3 times, dried, and then ground to obtain a green CuS@TA nanocarrier, i.e., a Cu-based nanocarrier.
[0013] Furthermore, in step (1), the copper salt is any one of copper chloride, copper nitrate and copper sulfate.
[0014] Furthermore, in step (1), the copper salt is CuCl2·2H2O.
[0015] The present invention also provides the use of the Cu-based nanocarrier in preparing a tumor in situ chemotherapy-photothermal combined therapy drug.
[0016] Furthermore, the preparation method of the tumor in situ chemotherapy-photothermal combined therapy drug comprises the following steps: adding DSF to methanol to dissolve it to obtain a methanol solution containing DSF; adding the methanol solution containing DSF to the CuS@TA nanocarrier solution, stirring it thoroughly and then centrifuging it, washing the precipitate with methanol 1 to 2 times, and drying it to obtain the DSF-CuS@TA tumor in situ chemotherapy-photothermal combined therapy drug.
[0017] Furthermore, the concentration of the CuS@TA nanocarrier solution is 1 mg / mL, and the weight ratio of the CuS@TA nanocarrier to the DSF is 1:0.02-0.3.
[0018] Furthermore, the tumor is breast cancer.
[0019] The present invention first studies the Cu co-release of the constructed nanomedicine under specific TME and external stimulation. 2+ The DSF-CuS@TA nanoparticles were found to release Cu by endogenous acid response after entering the tumor tissue. 2+ The two chelate in situ to generate Cu(DTC)2 with anticancer activity, which directly kills cancer cells. The experimental results show that DSF-CuS@TA nanoparticles show good anticancer effects in both in vivo and in vitro experiments. This intelligent diagnostic and therapeutic reagent DSF-CuS@TA based on photothermal imaging guidance has good application prospects in cancer treatment in the combined treatment mode of in situ chemotherapy and photothermal therapy drugs.
[0020] Beneficial effects:
[0021] The present invention constructs a Cu-based nanocarrier CuS@TA with good biocompatibility, tumor microenvironment response and thermosensitivity, and loads DSF to form a DSF-CuS@TA nanoplatform for the treatment of breast cancer. The nanocarrier CuS@TA prepared by the present invention is in the form of regular hexagonal nanosheets, with an average particle size of about 186.6nm and a Zeta potential of about -14.9mV. After loading DSF, the morphology of DSF-CuS@TA remains unchanged, the particle size increases to 208.7nm, the size is uniform, and the Zeta potential is -18.8mV; the DSF encapsulation rate is about 78.03%, and the drug loading is about 14.96%; the in vitro physiological stability is good, and the constructed DSF-CuS@TA has good photothermal heating performance and high photothermal conversion efficiency (η=45.73%). In addition, CuS@TA has the characteristics of pH and heat dual stimulus response degradation. It degrades after dual stimulation, resulting in gradual collapse of the morphology, smaller particle size, and gradually lighter or even disappearance of the solution color. DSF-CuS@TA promotes the production of the chemotherapy drug CuL2 under the same treatment conditions. The results of in vitro anti-tumor experiments show that DSF-CuS@TA can produce strong lethality to cancer cells under the combined treatment mode of tumor in situ chemotherapy and photothermal therapy. The results of mouse in vivo imaging experiments show that DSF-CuS@TA can smoothly reach the tumor lesion area and has a significant tumor inhibition effect under the combined treatment of tumor in situ chemotherapy and photothermal therapy, with a tumor inhibition rate of up to 80%. The results of section staining of important tissues show that DSF-CuS@TA has no obvious damage to the main organs of mice, and the weight of mice in each group has not changed significantly. The above results show that the DSF-CuS@TA of the present invention has a strong anti-tumor effect, negligible toxic side effects and good biocompatibility. In summary, the intelligent diagnosis and treatment nanoplatform DSF-CuS@TA constructed in the present invention represents a multimodal combined therapeutic nanomedicine integrating photothermal and in situ chemotherapy, which has a reference significance for the development of new nanomedicines and clinical cancer treatment research. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 CuS@TA, DSF-CuS@TA and pure water at 1064nm (1W cm -2 ) laser irradiation (a) Photothermal imaging and (b) photothermal heating curve; (c) Photothermal heating curve of DSF-CuS@TA solution under different concentrations; (d) Photothermal heating curve of DSF-CuS@TA solution under different powers of 1064nm laser irradiation; (e) DSF-CuS@TA at 1064nm (1W cm -2 ) Photothermal cycle curves under laser irradiation; (f) DSF-CuS@TA solution at 1064nm (1Wcm -2) Fitting curve of photothermal conversion efficiency after laser irradiation for 10 min;
[0023] Figure 2 (a) Particle size and (b) solution color of DSF-CuS@TA in different media.
[0024] Figure 3 Particle size of CuS@TA at different pH values: (a) pH 7.4 and (b) pH 6.5; absorbance of CuS@TA at 1064 nm at different pH values: (c) pH 7.4 and (d) pH 6.5;
[0025] Figure 4 TEM morphology images of DSF-CuS@TA after incubation for different time periods at pH 7.4 and pH 6.5;
[0026] Figure 5 The color of CuS@TA solution after incubation for a certain time under different pH and temperature conditions;
[0027] Figure 6 Absorbance of DSF-CuS@TA at 425 nm under different pH conditions: (a) pH 7.4 and (b) pH 6.5;
[0028] Figure 7 CLSM images of 4T1 cells after incubation with R6G-CuS@TA for different time periods (scale bar: 20 μm);
[0029] Figure 8 Cell survival rate of 4T1 cells after treatment with different doses of DSF, CuS@TA and DSF-CuS@TA under different pH conditions: (a) pH 7.4 and (b) pH 6.5; (c) relative cell survival rate after different treatments, including control group, DSF only, CuS@TA only, 1064nm laser only, CuS@TA + 1064nm laser, DSF-CuS@TA, CuL2 and DSF-CuS@TA + 1064nm laser groups;
[0030] Fig. 9 CLSM images of 4T1 cells stained with calcein-AM and PI (scale bar: 50 μm);
[0031] Fig.10 Flow cytometry was used to detect the apoptosis of 4T1 cells induced by CuS@TA;
[0032] Fig.11 (a) Fluorescence real-time image and (b) fluorescence intensity of major organs and tumors.
[0033] Fig.12(a) In vivo photothermal imaging of 4T1 tumor-bearing mice at different time points after treatment with saline, CuS@TA, and DSF-CuS@TA under 1064 nm laser irradiation; (b) The corresponding photothermal temperature rise curve of the tumor area within 10 min of laser irradiation;
[0034] Fig.13 (a) Tumor photos, (b) tumor volume, (c) tumor weight, and (d) tumor inhibition rate of 4T1 tumor-bearing mice in different groups;
[0035] Fig.14 Body weight change curves of 4T1 tumor-bearing mice in different groups;
[0036] Fig.15 HE staining of main organs and tumor tissues of 4T1 tumor-bearing mice in different groups (scale bar: 50 μm). DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0038] Example
[0039] A method for preparing a Cu-based nanocarrier with multiple stimulus-responsive degradability comprises the following steps:
[0040] (1) Weigh 0.1022 g of CuCl2·2H2O and 3 g of PVPK30 and dissolve them in 20 mL of ultrapure water. Stir them with a magnetic stirrer at room temperature until they are fully dissolved to obtain a mixed solution I.
[0041] (2) Dissolve 50 mg TA (tannic acid) and 0.725 g Na2S2O3·5H2O in 10 mL ultrapure water to obtain TA solution and Na2S2O3·5H2O solution respectively;
[0042] (3) slowly adding 10 mL of TA solution dropwise to the mixed solution I under stirring to obtain a mixed solution II;
[0043] (4) Add 10 mL of Na2S2O3·5H2O solution to the mixed solution II, stir evenly, and then quickly transfer to a reactor for heating. After the temperature rises to 140°C, continue the reaction for 6 hours to obtain a mixed solution III;
[0044] (5) The mixed solution III was naturally cooled to room temperature, filtered, and the filtrate was centrifuged to separate the precipitate, which was washed twice with ultrapure water, dried in an oven at 50 °C, and then ground to obtain a green CuS@TA nanocarrier, i.e., a Cu-based nanocarrier.
[0045] A method for preparing a DSF-CuS@TA tumor in situ chemotherapy-photothermal combined therapy drug comprises the following steps:
[0046] 0.2372 mg of DSF was added to methanol to dissolve, and a methanol solution containing DSF was obtained; 1 mg of CuS@TA nanocarrier was dissolved in water to prepare a 1 mg / mL CuS@TA nanocarrier solution; the methanol solution containing DSF was added to the CuS@TA nanocarrier solution, and the mixture was stirred thoroughly and centrifuged. The precipitate was washed twice with methanol and dried in an oven to obtain DSF-CuS@TA. Calculation of DSF drug loading rate and encapsulation efficiency:
[0047] First, excess Cu was added to methanol solutions containing different amounts of DSF (0.02965, 0.0593, 0.08895, 0.1186, 0.14825, 0.1779, 0.20755, 0.2372, 0.26685, 0.2965 mg) 2+ (CuCl2·2H2O), and after sufficient reaction, the UV absorbance at 425nm was measured to establish a standard curve; next, different amounts of DSF (same as above) were added to 1 mg CuS@TA carrier solution, and after sufficient reaction, the solution was centrifuged and washed with methanol twice, the supernatant was collected, and excess Cu 2+ (CuCl2·2H2O) reacts with the remaining DSF. Finally, the absorbance of the supernatant at 425 nm was measured by an ultraviolet spectrophotometer to calculate the DSF drug loading rate and encapsulation rate. The formula is as follows:
[0048]
[0049]
[0050] The drug loading rate of DSF-CuS@TA was calculated to be 14.96% and the encapsulation efficiency was 78.03%.
[0051] In vitro photothermal heating performance test of DSF-CuS@TA:
[0052] Prepare the samples at concentrations of 0, 5, 10, and 20 μg mL -1 1 mL of DSF-CuS@TA solution was placed in a 1.5 mL EP tube and ultrapure water was used as a reference. -2 ) irradiated the sample solution for 10 min. An infrared thermal imager was used to record the photothermal temperature rise image of the sample, and a multi-channel temperature recorder was used to record the temperature change curve of the sample solution over time. Similarly, at different powers (0.25, 0.5, 0.75, 1.0 W cm -2 ) conditions, the temperature curve of the sample solution after DSF-CuS@TA was irradiated with 1064nm laser was tested. In the photothermal stability experiment, 1mL 20μgmL-1 The temperature change of the DSF-CuS@TA solution after heating up under 1064nm laser irradiation for 10min, then turning off the laser and cooling naturally for 15min was repeated 5 times to obtain the photothermal cycle curve of the sample solution.
[0053] To calculate the photothermal conversion efficiency of DSF-CuS@TA aqueous solution at 1064 nm, 1 mL 20 μg mL -1 The sample solution was placed in a 1.5 mL EP tube and illuminated with a 1064 nm laser (1.0 W cm -2 ) After irradiation for 10 minutes, turn off the light, cool naturally for 15 minutes, and record the temperature rise and fall curves. The following formula is used to calculate the photothermal conversion efficiency of DSF-CuS@TA aqueous solution at 1064nm:
[0054]
[0055] Since CuS@TA and DSF-CuS@TA have strong ultraviolet absorption in the second near-infrared, ultrapure water was used as a blank control, and the wavelength was 1064 nm and the power was 1.0 W cm -2 The sample solution was irradiated with a laser of 1064 nm, and the photothermal temperature rise image of the sample was recorded by an infrared thermal imager. The temperature change of CuS@TA, DSF-CuS@TA and pure water over time was recorded by a temperature recorder. The results showed that after 10 minutes of 1064 nm laser irradiation, the temperature of pure water only increased by about 5 °C and remained basically constant. This shows that pure water has weak absorption in the near-infrared region and cannot convert near-infrared light into heat, so the temperature did not change significantly after laser irradiation. In contrast, the concentration of 20 μg mL -1 The photothermal image of the CuS@TA aqueous solution gradually changes from blue to orange-red as the illumination time increases, and the temperature rises rapidly by about 22°C within 600s, with a very obvious heating effect. In addition, after loading DSF (DSF-CuS@TA), it still has good photothermal heating performance. The data show that DSF-CuS@TA can convert light energy into heat energy ( Figure 1 -ab).
[0056] The present invention also tested the photothermal heating performance of DSF-CuS@TA with different concentrations after 1064nm laser irradiation (laser power: 1.0W cm -2 , irradiation time: 10min). The temperature change was recorded by a temperature recorder. Figure 1 -c It can be seen that the higher the concentration of DSF-CuS@TA, the higher the maximum temperature reached after 1064nm laser irradiation. In addition, the higher the laser power, the higher the maximum temperature reached by DSF-CuS@TA after laser irradiation also changes significantly ( Figure 1-d). The results show that DSF-CuS@TA has a concentration- and laser power-dependent heating effect under laser irradiation.
[0057] The photothermal heating stability of DSF-CuS@TA was evaluated by photothermal cycling experiments. Figure 1 As shown in Figure 5, after 5 heating-cooling cycles, the maximum temperature that DSF-CuS@TA can reach did not decrease significantly, which indicates that DSF-CuS@TA has good photothermal stability under laser irradiation and has the possibility of being further used in photothermal therapy. Figure 1 -f, according to the thermal conductivity constant and the temperature drop curve of the cooling process, 20μg mL -1 The photothermal conversion efficiency (η) of DSF-CuS@TA at 1064 nm reached 45.73%, which indicates that DSF-CuS@TA nanoparticles are a promising candidate for photothermal materials.
[0058] Stability test of DSF-CuS@TA:
[0059] The prepared DSF-CuS@TA was dissolved in ultrapure water, physiological saline, PBS and 1640 culture medium and incubated, and the particle size of the sample solution at different time points (0, 1, 2, 4, 6, 8, 12, 24, 48 h) was measured to judge the stability of the sample.
[0060] In order to simulate the stability in physiological environment, the hydrated particle size of DSF-CuS@TA was measured after incubation in ultrapure water, physiological saline, PBS and 1640 basal medium for different time periods. The results showed that the particle size of DSF-CuS@TA did not change significantly within 24 h ( Figure 2 -a), and the solution color did not change significantly ( Figure 2 -b), relatively stable, which indicates that the sample has good biological stability.
[0061] Multiple stimulus response degradation performance test of CuS@TA:
[0062] The CuS@TA aqueous solution was incubated for a certain period of time (1, 4, and 7 days) under different pH (6.5 and 7.4) and temperature (4°C, 37°C, and 55°C). The color change of the solution was recorded and the hydrated particle size of the samples after incubation under different conditions was determined by dynamic light scattering. At the same time, a small amount of the above sample solution was taken out with a pipette and dropped on the front of the copper mesh. After drying naturally, the morphological changes were captured by transmission electron microscopy and used to determine the degradation of CuS@TA nanoparticles under high temperature and slightly acidic environment. To further determine the dual stimulus response degradation characteristics of the sample, a certain concentration of CuS@TA was immersed in PBS buffer solutions of pH 7.4 and pH 6.5, respectively. After incubation for a certain period of time (0, 1, 2, 4, 6, 8, 10, 12, 24, 36, and 48 h) under different temperatures (4°C, 37°C, and 55°C), 1 mL of the solution was taken out for high-speed centrifugation, and the Cu in the supernatant was detected by ICP-OES. 2+ The content of CuS@TA was determined to release Cu under multiple stimuli. 2+ The case (DSF-CuS@TA was not selected as a sample to detect Cu 2+ The release of Cu from DSF-CuS@TA under acidic conditions 2+ It will chelate with DSF in situ to form CuL2 complex, thus affecting Cu 2+ In addition, the absorbance of CuS@TA at 1064 nm was measured under the same conditions.
[0063] The multi-stimulus responsive degradation performance of CuS@TA aqueous solution was evaluated by measuring the particle size changes after being treated under different conditions. Figure 3 -ab It can be seen that under neutral conditions (pH 7.4), the particle size of CuS@TA changes little after being incubated at different temperatures for a certain period of time. However, at pH 6.5, its particle size changes significantly, and the change is more obvious at higher temperatures. After incubation for 24 hours at 55°C and pH 6.5, the particle size of CuS@TA decreases from 180nm to 78nm. This may be due to the destruction of the internal structure of CuS@TA under slightly acidic conditions, resulting in the degradation of CuS@TA. In addition, Figure 3 -cd shows that under pH 7.4, the absorbance of CuS@TA at 1064nm does not change significantly with time and temperature, indicating that CuS@TA has good stability under neutral conditions. On the contrary, under pH 6.5, the absorbance changes significantly with time and temperature, and is temperature-dependent. This also proves that under pH 6.5, higher temperature stimulation will destroy the structure of CuS@TA. It further shows that CuS@TA has the characteristics of pH and heat dual stimulus response degradation.
[0064] In order to confirm the above results, the morphology of CuS@TA was measured at 55°C. Figure 4 It can be seen that the CuS@TA nanoparticles still maintain a relatively complete hexagonal morphology after being immersed in pH 7.4 for 7 days, but after being immersed in pH 6.5 for 4 days, the hexagonal morphology boundaries begin to blur, and after 7 days, the hexagonal morphology no longer exists, and the structure of CuS@TA has been completely destroyed. From the solution color change diagram, it can be seen that the color of the CuS@TA solution changes slightly under neutral conditions, and changes significantly after slightly acidic treatment. After incubation in a solution at 55°C and pH 6.5 for 7 days, the solution color is close to transparent ( Figure 5 ). The above results all indicate that CuS@TA has the dual stimulus responsive degradation characteristics of pH and heat.
[0065] Production of the chemotherapy drug CuL2:
[0066] DSF-CuS@TA was incubated in PBS at different pH (6.5, 7.4) and temperature (4°C, 37°C, 60°C) for a certain period of time to fully release Cu 2+ and DSF, and 1 mL was taken out at different time points (0, 1, 2, 4, 6, 8, 10, 12, and 24 h), and its UV absorption value at 425 nm was measured using a UV spectrophotometer to verify the generation of CuL2.
[0067] The multi-stimulus responsive degradation performance of DSF-CuS@TA was investigated by the generation of CuL2. 2+ They can interact to generate highly toxic CuL2, whose characteristic ultraviolet absorption peaks are located at 265nm and 425nm. In order to confirm that the formation of CuL2 in vitro has temperature and pH response characteristics, DSF-CuS@TA was incubated in PBS at different temperatures (4℃, 37℃, 55℃) and different pH (7.4, 6.5) for different time periods, and the absorbance of DSF-CuS@TA solution at 425nm was detected by ultraviolet spectrophotometry. Figure 6 As shown in the figure, the UV absorption peak intensity of DSF-CuS@TA solution at 425 nm gradually increases with time, and under moderately acidic conditions (pH 6.5) and high heat (55°C) stimulation, the absorption value at 425 nm changes more significantly, proving the cumulative formation of CuL2, indicating that CuS@TA loaded with DSF (DSF-CuS@TA) still has multiple stimulus-responsive degradation characteristics.
[0068] DSF-CuS@TA in vivo and in vitro anti-tumor experiments:
[0069] 1. Experimental Methods
[0070] (1) Cell culture
[0071] Take out the cryovial containing 4T1 cells from liquid nitrogen, quickly put it into a 37℃ constant temperature water bath, shake it gently to melt it, disinfect the wall of the cryovial with 75% alcohol, put it into an ultra-clean workbench, and wipe the wall of the tube with a cotton ball containing 75% alcohol. Open the screw cap in the ultra-clean workbench, aspirate the cell suspension in the tube, transfer it to a centrifuge tube containing 3mL of complete culture medium, mix it, place it in a centrifuge and centrifuge it at 1000rpm / min for 5min, discard the supernatant, add 3mL of complete culture medium, blow it evenly, transfer it to a 10cm clean and sterilized culture dish pre-added with 7mL of complete culture medium, and culture it in a 37℃, 5% CO2 incubator.
[0072] (2) Cell passaging
[0073] Observe the cell status under a microscope. When the cells grow to a density of about 80%, discard the original culture medium. Wash 2 to 3 times with sterile PBS buffer to wash away floating dead cells, then add 0.25% trypsin digestion solution containing EDTA to the culture dish, shake slowly to evenly cover the cell surface with the digestion solution, and place the culture dish in the incubator to digest the cells attached to the bottom of the dish. After about 2 minutes, add 2 times the amount of culture medium as the digestion solution to terminate the digestion to prevent cell digestion and damage cell vitality. Use a pipette to gently blow the bottom of the culture dish to cause the cells to fall off the bottom of the culture dish, transfer the cell suspension to a centrifuge tube, centrifuge at 1200rpm / min for 5 minutes, pour off the upper mixed solution, collect the cell pellet, and add an appropriate amount of complete culture medium to resuspend. Add the cell suspension to 2 to 3 cell culture dishes containing new complete culture medium and place them in a 37°C, 5% CO2 incubator for continued culture.
[0074] (3) Cellular uptake
[0075] Using R6G as a fluorescent probe, detect whether the drug can enter the cell and the change of the fluorescence intensity in the cell over time. The specific operation method is as follows:
[0076] Place the cell slide in a 24-well plate in a clean bench, soak it in 75% alcohol for 30 min, wash it three times with PBS, and let it dry naturally for later use. 4 The cells were inoculated at a density of 1000 cells / well in a 24-well plate containing a slide and cultured in a cell culture incubator at 37°C and 5% CO2 for 24 h to facilitate their attachment to the cell wall. CuS@TA labeled with R6G (0.5 mL, 20 μg mL -1) After treatment for 0, 4, 8, and 12 h, the cells were washed three times with PBS to remove excess dye, then fixed with 4% paraformaldehyde for 20 min, washed 2 to 3 times with PBS, stained with 100 μL DAPI for 20 min, and washed three times with PBS again to remove excess DAPI. The slide containing the cells was carefully taken out, and the cell-containing side was inverted on a slide with anti-fluorescence quencher for sealing, and finally the uptake was observed by laser confocal microscopy (CLSM).
[0077] (4) In vitro cytotoxicity
[0078] The MTT method was used to detect the cell survival rate. First, 4T1 cells in the logarithmic growth phase were washed 2 to 3 times with sterilized PBS, digested with trypsin, and resuspended in 10 5 100 μL of PBS was added to each well of the 96-well plate and incubated in a cell culture incubator at 37°C and 5% CO2 for 24 h to allow the cells to adhere to the wall. To reduce water loss during the culture process, 200 μL of PBS was added to each well of the outermost well of the 96-well plate. After the cells were completely attached to the wall, the culture medium was discarded and 100 μL of PBS containing different concentrations (0, 1, 2.5, 5, 10, 20 μg mL -1 )DSF, CuS@TA and DSF-CuS@TA culture medium, 100 μL PBS was added to the blank group, 5 replicate wells were set for each drug concentration, and the culture medium containing drugs was discarded after 24 h of continuous culture, and 10 μL of 5 mg mL -1 The cells were placed in an incubator and incubated for 4 h. After 4 h, purple crystals were observed to precipitate from the bottom of the 96-well plate. The upper clear layer in each well of the 96-well plate was gently aspirated, and 100 μL DMSO was added to each well. The cells were gently shaken on a shaker for 10 min to promote the full dissolution of the purple formazan crystals. Finally, the absorbance (OD value) of each well at 490 nm was measured using an ELISA reader, and the cell survival rate was calculated according to the following formula:
[0079]
[0080] (5) Synergistic therapeutic effect of in vitro chemotherapy and photothermal therapy
[0081] 4T1 cells in the logarithmic growth phase were digested with trypsin and diluted to 10 5 The cells were inoculated in a 96-well plate at a volume of 100 μL per well and cultured in a constant temperature cell culture incubator at 37°C and 5% CO2 for 24 h. The culture medium was discarded and different treatments were given at pH 6.5 and 7.4. The specific groups were: control group, 1064 nm laser group, DSF group, CuS@TA (20 μg mL -1) group, DSF-CuS@TA (20 μg mL -1 ) group, CuS@TA+1064nm laser group, CuL2 group, DSF-CuS@TA+1064nm laser group, each group was set up with 5 replicate wells, and the culture was continued for 24 hours. Among them, after 20 hours of drug treatment, each well of the laser group was irradiated with 1064nm laser at 1Wcm -2 The power was irradiated for 10 min and the culture was continued for 4 h. After the culture was completed, the medium containing the drug was discarded and 10 μL of 5 mg mL -1 The cells were incubated with MTT solution for 4 h. Finally, the upper MTT solution was discarded, 100 μL DMSO was added to each well, and the cells were gently shaken on a shaker for 10 min to allow the formazan crystals to fully dissolve. Finally, the absorbance (OD value) of each well at 490 nm was measured using an ELISA reader, and the cell survival rate was calculated in the same way as above.
[0082] (6) Dead and live cell staining
[0083] 4T1 cells in the logarithmic growth phase were digested with trypsin and diluted with culture medium before being inoculated on a confocal microplate (10 5 The cells were placed in a cell culture incubator at 37°C and 5% CO2 for 24 h to promote cell adhesion. Different treatments were given at pH 6.5 and 7.4, and the groups were: control group, DSF group, 1064 nm laser group, CuS@TA (20 μg mL -1 ) group, DSF-CuS@TA (20 μg mL -1 ) group, CuS@TA+1064nm laser group, CuL2 group, and DSF-CuS@TA+1064nm laser group. The culture was continued for 24 hours. After 20 hours of drug treatment, each well of the laser group was treated with 1064nm laser at 1W cm -2 The cells were irradiated with a power of 10 min and cultured for 4 h. After the culture was completed, the cell supernatant was removed, the cells were washed 3 times with PBS, and the cells were stained with Calcein-AM / PI (200 μL) for 15 minutes. After staining, the supernatant was removed, the cells were washed 3 times with PBS, the basal culture medium was added, and the image color was observed by CLSM. The living cells after staining showed green fluorescence (λex=488nm, λem=515nm), and the dead cells emitted red fluorescence (λex=535nm, λem=617nm).
[0084] (7) Detection of 4T1 cell apoptosis by flow cytometry
[0085] 4T1 cells were seeded in a six-well plate at a density of 2×105 cells / well and incubated in a cell culture incubator at 37°C and 5% CO2. When the cells were completely attached, different treatments were given, including: control group, DSF (20 μg mL-1, CuS@TA equivalent) group, Laser group, CuS@TA (20 μg mL-1) group, DSF-CuS@TA (20 μg mL-1) group, CuS@TA+Laser group, Cu(DTC)2 group, and DSF-CuS@TA+Laser group. After 24 hours, trypsin digestion was performed, and the cells were collected by centrifugation and washed 1 to 2 times with pre-cooled PBS. Then, 200 μL 1× apoptosis staining buffer and 10 μL Annexin V-FITC were added, mixed and incubated in an incubator in the dark for 15 minutes, and then 10 μL PI was added and incubated for another 15 minutes. After the incubation, 100 μL 1× apoptosis staining buffer was added and mixed, and the cells were passed through a membrane and detected for cell apoptosis using a flow cytometer.
[0086] (8) Establishment of in vivo tumor model
[0087] Select 18-20g BABL / c nude female mice, and after the mice adapt to the growth environment, add 100 μL of 4T1 cell suspension (cell density is about 2×10 6 ) was injected into the subcutaneous tissue at the base of the right hind leg of mice. When the subcutaneous tumor of the mice grew to the size of soybeans, in vivo experiments were performed.
[0088] (9) In vivo photothermal imaging
[0089] In the in vivo photothermal imaging experiment, when the mouse tumor volume grew to about 100mm 3 Saline and CuS@TA (20 mg kg -1 ) and DSF-CuS@TA (20 mg kg -1 ) 100 μL each. 4 h after injection, the mice were illuminated with a 1064 nm laser at 1 W cm -2 The mice were irradiated for 10 min under the given conditions, and the photothermal imaging temperature changes of the mice were monitored by an infrared thermal imager.
[0090] (10) In vivo fluorescence imaging
[0091] When the mouse tumor volume is about 100mm 3 At 200 μg / kg, mice were injected with R6G-labeled CuS@TA (R6G-CuS@TA, 20 mg / kg -1 The fluorescence intensity in the mouse tumor was monitored by in vivo imaging at 0, 1, 2, 4, 8, and 12 hours after injection. The nude mice were then killed by cervical dislocation, and the tumors and major organs (heart, liver, spleen, lung, and kidney) were collected to collect fluorescence information.
[0092] (11) In vivo treatment experiments
[0093] In the live mouse treatment experiment, when the mouse tumor grows to about 100mm 3 At the same time, the mice were randomly divided into 8 groups (Control group, 1064nm laser group, CuS@TA group, DSF group, CuS@TA+1064nm laser group, DSF-CuS@TA group, CuL2 group, DSF-CuS@TA+1064nm laser group), with 3 mice in each group. Starting from the 0th day of treatment, the weight of the mice and the long diameter (L) and short diameter (W) of the tumor were measured and recorded every other day. Every 3 days, 100μL of DFS, CuS@TA, and DSF-CuS@TA dispersed in normal saline were injected through the tumor in situ, and then the mice in the laser group were treated with photothermal therapy (1064nm, 1W cm) 4h after injection according to the photothermal treatment time previously determined by photothermal imaging. -2 , 10min). After 14 days of treatment, the mice were dissected, the tumor weight was weighed, and photos were taken. The main organs (heart, liver, spleen, lung, and kidney) of the mice were collected, fixed with 4% paraformaldehyde, dehydrated, and embedded in paraffin. The sections were stained with H&E to evaluate the toxicity and side effects of DSF-CuS@TA on mice. The tumor volume and tumor inhibition rate were calculated according to the formula.
[0094]
[0095]
[0096] (12) HE staining
[0097] Wax blocks of the main organs and tumor tissues of mice were obtained, and each wax block was sliced to a thickness of 3 μm. The slices were spread, fished out, and baked at 55°C for 2 hours, followed by H&E staining.
[0098] H&E staining procedure (it is recommended to use words to describe the processes of transparency, dehydration, differentiation, staining, etc., and arrows are used to indicate what is not standard): xylene I (5min) - xylene II (5min) - xylene III (10min) - anhydrous ethanol (10min) - 95% ethanol (10min) - 90% ethanol (10min) - 80% ethanol (10min) - 70% ethanol (10min) - PBS soaking (5min, 3 times) - hematoxylin staining (10min) - water washing (2min) - 1% hydrochloric acid ethanol differentiation (2s) - running water washing (2min) - eosin staining (2s) - 80% ethanol (1min) - 90% ethanol (1min) - 95% ethanol (1min) - anhydrous ethanol (1min) - xylene (1min) - air drying, neutral resin sealing.
[0099] 2. Test results
[0100] (1) In vitro cellular uptake
[0101] Rhodamine 6G (R6G) was doped into CuS@TA to investigate the lethal mechanism of DSF-CuS@TA on 4T1 cells. The blue color represents the cell nucleus and the red color represents the fluorescence of the nanoparticles. By observing the intensity of the red fluorescence in the cells, the uptake of these particles by 4T1 cells was investigated. Figure 7 As shown, R6G-CuS@TA can be effectively taken up by 4T1 cells, and the fluorescence intensity significantly increases with time. The above results indicate that CuS@TA can be used as a carrier of DSF and can effectively deliver DSF into tumor cells.
[0102] (2) Synergistic antitumor activity of chemotherapy-photothermal therapy in vitro
[0103] The MTT method was used to detect the effects of different treatments on the viability of 4T1 cells to verify the in vitro photothermal enhanced chemotherapy of DSF-CuS@TA. Figure 8 -a It can be seen that after co-culturing different concentrations of free DSF and CuS@TA with three types of cancer cells for 24 hours, the cell survival rate is still around 90%, indicating that the toxic side effects of free DSF and CuS@TA are small and the biosafety is high. On the contrary, DSF-CuS@TA showed a significant killing effect on 4T1 cells, and the toxicity was concentration-dependent. In addition, it showed more obvious toxicity to cancer cells under slightly acidic conditions (pH 6.5). This is because DSF-CuS@TA can dissociate and release more DSF and Cu in a slightly acidic environment. 2+ The two chelate in situ in the cells to generate the chemotherapy drug CuL2, which causes stronger toxic side effects on cancer cells.
[0104] In addition, 4T1 cells were incubated with high doses of DSF-CuS@TA and further irradiated with 1064 nm laser to evaluate the 1064 nm laser-triggered cytotoxicity of DSF-CuS@TA. Figure 8 -c shows that compared with DSF-CuS@TA alone, DSF-CuS@TA produced much higher cytotoxicity to the three cell types after 1064nm laser irradiation. Under 1064nm laser irradiation, the survival rate of 4T1 cells after treatment with 20μg DSF-CuS@TA was only about 12%, while the cell survival rates after DSF-CuS@TA alone and CuS@TA+1064nm laser treatment were 45% and 63%, respectively, indicating that DSF-CuS@TA can activate chemotherapy-induced cell death by synergistic photothermal therapy and in situ Figure 8 -b).
[0105] (3) Dead and live cell staining
[0106] In order to visually observe the photothermal treatment effect of DSF-CuS@TA, calcein-AM and propidium iodide (PI) were used to stain live and dead cells, and confocal microscopy was used to record fluorescent photos of different treatment groups. Calcein-AM is a cell dye that can fluorescently label live cells. When it enters the cytoplasm, it is hydrolyzed by esterase and emits strong green fluorescence. Propidium iodide (PI) is a nuclear staining reagent that can stain DNA. It releases red fluorescence after embedding into double-stranded DNA, but PI cannot pass through the membrane of living cells and can only stain dead cells. Fig. 9 As shown in the figure, strong green fluorescence can be observed in the control group, CuS@TA group, DSF group and laser irradiation group, indicating that these treatments have no obvious killing effect on cancer cells. Green and red fluorescence can be observed in the CuL2, DSF-CuS@TA and CuS@TA+laser treatment groups. In contrast, obvious red fluorescence is shown in the DSF-CuS@TA+laser treatment group. This may be due to the fact that 4T1 cancer cells have a more obvious killing effect on in vitro 4T1 cells after the combination of in situ CuL2 generation and thermal therapy, so that all cells show red fluorescence. This is basically consistent with the experimental results of the MTT method to determine the cell survival rate. In summary, the combined treatment mode of photothermal therapy and in situ chemotherapy of DSF-CuS@TA in cell-level experiments can effectively inhibit the growth of 4T1 cells and can better kill 4T1 cells.
[0107] (4) Flow cytometry detection of cell apoptosis
[0108] Annexin V-FITC / PI double staining was used to detect cell apoptosis after different drug treatments on a flow cytometer. The cells in the four regions were Q1: necrotic cells; Q2: late apoptotic cells; Q3: living cells; and Q4: early apoptotic cells. Fig.10As shown, compared with the Control group, after 24 hours of treatment with the same drug concentration, cells in each experimental group showed varying degrees of apoptosis. The survival rates of 4T1 cancer cells after treatment with free DSF, CuS@TA and 1064nm laser irradiation were 91.2%, 90.69% and 90.2%, respectively, indicating that CuS@TA has good cell compatibility and 4T1 cells have good tolerance to 1064nm laser irradiation. Compared with the CuS@TA group, the cell apoptosis rate in the CuS@TA+Laser group increased by 20%, indicating that CuS@TA can be used as a photothermal converter to convert the light energy generated by the 1064nm laser into thermal energy, killing cancer cells in the form of hyperthermia. Compared with the DSF group, at the same DSF concentration, the cell mortality rate reached 41% after 24 hours of treatment with free Cu(DTC)2, which significantly induced apoptosis of 4T1 cells, indicating that DSF has a strong anti-cancer effect after conversion to Cu(DTC)2 ( Fig.10 ). The accumulation of DSF in tumors was improved by the delivery of copper-based nanocarriers, and the released Cu 2+ In situ chelation of DSF generates more Cu(DTC)2, leading to cell apoptosis. Among them, the cell apoptosis rate of the DSF-CuS@TA+Laser group was the highest, reaching 73.7%, further indicating that DSF-CuS@TA can induce cancer cell death through in situ activated chemotherapy combined with photothermal therapy.
[0109] (5) In vivo imaging
[0110] The results of in vivo imaging of mice injected with R6G-CuS@TA via tail vein are shown in Fig.11 -a, as can be seen from the figure, 4 hours after injection, the mouse tumor tissue began to have weak fluorescence and the fluorescence intensity gradually increased with time. In addition, under the same conditions, the fluorescence intensity of the main organs and tumor tissues of the mice was observed 12 hours after injection, as shown in Figure 1. Fig.11 -b, after 12 hours, the fluorescence intensity of each organ was weak, while the fluorescence intensity of the tumor tissue was relatively strong, which means that the drug can be directed to accumulate in the tumor site and thus exert an anti-tumor effect.
[0111] (6) DSF-CuS@TA in vivo photothermal imaging experiment
[0112] Based on the excellent photothermal heating performance and good biocompatibility of DSF-CuS@TA in vitro, the photothermal imaging performance of DSF-CuS@TA in vivo was further investigated. A 4T1 tumor-bearing mouse model was established and the mice were randomly divided into: PBS+Laser group, CuS@TA+Laser group and DSF-CuS@TA+Laser group. According to the guidance of the cell experiment results, 4 hours after CuS@TA and DSF-CuS@TA were injected into mice, a 1064nm laser was used at 1W cm -2 The tumor-bearing mice were irradiated with laser for 10 min at a power of 1000 nm, and the photothermal images and temperature changes during the laser irradiation were recorded synchronously with an infrared thermal imager. Fig.12 -a, it can be observed that the light spot at the tumor site of mice in the Laser group is not obvious, while the light spot at the tumor site of mice in the CuS@TA+Laser group and DSF-CuS@TA+Laser group is brighter. The brighter the light spot, the higher the temperature at the tumor site of the mouse. The corresponding temperature rise curve of the tumor site is shown in Figure 2. Fig.12 -b. Under the same treatment conditions, after 10 minutes of laser irradiation, the temperature of the tumor site in the mice in the PBS+Laser group only increased to about 2°C, the temperature of the tumor site in the mice in the CuS@TA-1+Laser group increased to 52.4°C, and the temperature of the tumor site in the mice in the DSF-CuS@TA+Laser group was 55.3°C. This result shows that DSF-CuS@TA has good photothermal warming performance in 4T1 tumor-bearing mice.
[0113] (7) Study on the anti-tumor activity of DSF-CuS@TA in vivo chemotherapy combined with photothermal therapy
[0114] The combined treatment mode of in situ chemotherapy and photothermal therapy based on DSF-CuS@TA has excellent anti-tumor effect at the cellular level. The chemotherapy-synergistic photothermal therapy effect of DSF-CuS@TA in vivo was further explored using BALB / c nude mice carrying 4T1 tumors.
[0115] In order to evaluate the anti-tumor effect in vivo, the tumor volume of mice was monitored for 14 consecutive days after different treatments. The change curve of tumor volume over time of each group of mice was made based on the recorded data to observe the treatment effect of each group. The change curve of relative tumor volume over time of each group was obtained from the change of tumor volume during treatment. The results are shown in the figure below. Fig.13-ab shows that with the increase in the number of treatment days, the relative tumor volume of mice in each group showed an increase to varying degrees. The tumor volume of tumor-bearing mice treated with the Control group, Laser group, DSF group, and CuS@TA group showed a significant growth trend, and the relative tumor volume after the treatment increased by about 4 times compared with before treatment. The relative tumor volume of tumor-bearing mice treated with the CuS@TA+Laser group increased by about 3 times, indicating that there was almost no inhibitory effect on mouse tumor growth. The tumor volume of tumor-bearing mice treated with the DSF-CuS@TA group was about 2.5 times that before treatment, and the tumor inhibition rate was about 55%, showing a certain therapeutic effect. After 14 days of treatment in the DSF-CuS@TA+Laser group, the relative tumor volume was about 1.2 times, and the tumor inhibition rate reached 75% ( Fig.13 -c), indicating that the thermal therapy and in situ chemotherapy of DSF-CuS@TA+Laser significantly inhibited tumor growth and had good anti-tumor ability. In summary, DSF-CuS@TA combined with 1064nm laser has photothermal therapy and in situ treatment effects, which can effectively inhibit tumor growth and achieve efficient treatment of tumors.
[0116] After the administration, the mice in each administration group were killed, and the tumor tissues obtained by dissection were weighed and photographed. Fig.13 -d, compared with the Control group, the tumor weights of mice in the Laser group, DSF group, and CuS@TA group were slightly different, while the DSF-CuS@TA group, CuL2 group, and DSF-CuS@TA+Laser group significantly inhibited tumor growth, and finally the tumor weight in the DSF-CuS@TA+Laser group was the smallest, further proving that DSF-CuS@TA has a good anti-tumor effect in vivo.
[0117] As an important indicator for evaluating the potential in vivo toxicity of the material, the present invention records the changes in the weight of the mice during the administration period. Fig.14 As shown, during the entire administration period, the weight of mice in each group did not show a significant downward trend, and the tumor-bearing mice ate freely and had a good survival state. The above results show that the prepared DSF-CuS@TA combined with laser irradiation has no obvious toxic side effects after administration and has good biosafety.
[0118] (8) H&E staining section analysis
[0119] After the administration, the dissected mouse organs and tumor tissues were subjected to H&E staining. In the H&E staining method, the cytoplasm is easily stained pink by eosin dye, and the cell nucleus is easily stained blue-purple by hematoxylin. Fig.15The results of tumor tissue sections of mice in each group show that the nuclei of tumor cells in the Control group are intact, in good condition, tightly arranged, and without obvious cell necrosis characteristics. There is no significant difference between the tumor cells in the Laser group, DSF group, and CuS@TA group and the Control group. However, the cell density of the CuS@TA+Laser group, CuL2 group, DSF-CuS@TA group, and DSF-CuS@TA+Laser group decreased to varying degrees, and the cells were loosely arranged. The nuclei of the cells in the CuL2 group and DSF-CuS@TA+Laser group shrank and became smaller or even disappeared. Among them, the cell state changes in the DSF-CuS@TA+Laser group were the most obvious, and the cell damage was the most serious. The results show that DSF-CuS@TA+Laser can effectively kill tumor cells under laser irradiation, and exert photothermal and in situ chemotherapy effects. In addition, the tissue sections of the heart, liver, spleen, lung, and kidney of tumor-bearing mice in each group showed that no obvious lesions occurred in the tissues of each group compared with the Control group, proving that the DSF-CuS@TA nanosystem is relatively safe in vivo.
[0120] In summary, the present invention uses MTT experiments and other methods to evaluate the toxicity of DSF-CuS@TA to cancer cells. In the cell uptake results, the fluorescence intensity comparison shows that the drug can effectively enter the cells. The results of the cytotoxicity experiment show that DSF-CuS@TA can effectively kill cancer cells compared with DSF and CuS@TA, and further enhances the killing effect on cancer cells after laser irradiation, indicating that DSF-CuS@TA can induce cancer cell death through photothermal therapy and in situ chemotherapy, achieving the effect of "1+1>2". Dead and live cell staining and flow cytometry also verified this result. The results of the in vivo experiment showed that DSF-CuS@TA can effectively enter the tumor tissue after tail vein injection, and has excellent photothermal warming performance in vivo, achieving the anti-tumor effect of in situ chemotherapy and photothermal therapy.
[0121] The drug-carrying system prepared by the present invention has good stability and multiple stimulation degradation characteristics. Based on the high photothermal conversion efficiency of the DSF-CuS@TA nanosystem, it can generate photothermal energy under near-infrared laser irradiation to enhance the anticancer activity of the drug-carrying nanosystem. At the same time, DSF-CuS@TA can specifically release Cu in the slightly acidic environment of the tumor. 2+ and DSF, the non-toxic DSF can quickly react with Cu 2+ In situ chelation of toxic Cu(DDC)2 leads to tumor cell death; in vitro and in vivo experimental results show that photothermal therapy can well enhance the therapeutic effect of in situ chemotherapy. The DSF-CuS@TA prepared by the present invention is a multi-modal combined therapeutic nanomedicine integrating photothermal therapy and in situ chemotherapy.
[0122] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make some modifications and improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the definition of the claims.
Claims
1. A method for preparing a Cu-based nanocarrier with multiple stimulus-responsive degradability, characterized in that: The steps include: (1) Weigh 0.1-0.2 g of copper salt and 2-4 g of polyvinyl pyrrolidone PVPK30 and dissolve them in 15-25 mL of ultrapure water, and stir them with a magnetic stirrer at room temperature until they are fully dissolved to obtain a mixed solution I; (2) dissolving 45-55 mg of tannic acid TA and 0.7-0.8 g of Na2S2O3·5H2O in 10-15 mL of ultrapure water, respectively, to obtain a TA solution and a Na2S2O3·5H2O solution; (3) slowly adding 8-15 mL of TA solution dropwise to the mixed solution I under stirring to obtain a mixed solution II; (4) adding 8-15 mL of Na2S2O3·5H2O solution to the mixed solution II, stirring evenly, and then quickly transferring to a reaction kettle for heating. After the temperature rises to 130-150° C., the reaction is continued for 5-8 hours to obtain a mixed solution III; (5) The mixed solution III is naturally cooled to room temperature, filtered, and the filtrate is centrifuged to separate the precipitate, which is washed with ultrapure water for 2 to 3 times, dried, and then ground to obtain a green CuS@TA nanocarrier, i.e., a Cu-based nanocarrier.
2. The method for preparing a Cu-based nanocarrier with multi-stimulus responsive degradability as claimed in claim 1, characterized in that: In step (1), the copper salt is any one of copper chloride, copper nitrate and copper sulfate.
3. The method for preparing a Cu-based nanocarrier with multi-stimulus responsive degradability as claimed in claim 1, characterized in that: In step (1), the copper salt is CuCl2·2H2O.
4. Use of the Cu-based nanocarrier prepared by the preparation method according to any one of claims 1 to 3 in the preparation of a drug for combined in situ chemotherapy and photothermal therapy of tumors, characterized in that: The preparation method of the tumor in situ chemotherapy-photothermal combined therapy drug comprises the following steps: adding disulfiram DSF into methanol to dissolve, so as to obtain a methanol solution containing DSF; adding the methanol solution containing DSF into a CuS@TA nanocarrier solution, stirring the solution thoroughly and then centrifuging, washing the precipitate with methanol for 1 to 2 times, and drying the solution to obtain the DSF-CuS@TA tumor in situ chemotherapy-photothermal combined therapy drug.
5. The use according to claim 4, characterized in that: The weight ratio of the CuS@TA nanocarrier to the DSF is 1:0.02-0.
3.
6. The use according to claim 4, characterized in that: The tumor is breast cancer.
Citation Information
Patent Citations
Application of pH-responsive copper-based compound nanomaterial serving as disulfiram carrier in preparation of multi-level selective tumor treatment medicine
CN112791193A
Preparation method and application of hollow mesoporous copper sulfide nano-drug carrier
CN114873629A